2020
DOI: 10.1155/2020/5182537
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Stability of the Geogrids-Reinforced Earth Slope under the Coupling Effect of Rainfall and Earthquake

Abstract: This paper focuses on understanding the dynamic response problem of flexible wrapped reinforced Earth slope under the coupling effect of earthquake and rainfall; a numerical calculation model of reinforced Earth slope considering the coupling effect of earthquake and rainfall was established. The dynamic response, pore pressure, and tensile stress distribution of the reinforcement under the rainfall before earthquake, the rainfall after the earthquake, and earthquake-rainfall are studied. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Rainfall infiltration is an important factor that induces slope instability [15,16]. Based on the theory of unsaturated seepage, Zhang et al established a hydraulic-mechanical coupling numerical calculation model for reinforced soil slopes and studied the effects of rainfall infiltration on the stress, displacement, and pore pressure of geogrid-reinforced soil slopes [17,18]. Zhang et al analyzed the seepage field distribution of root-fixed soil under rainfall conditions and found that when the root system continued to absorb water, the shear strength of unsaturated soil also increased [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall infiltration is an important factor that induces slope instability [15,16]. Based on the theory of unsaturated seepage, Zhang et al established a hydraulic-mechanical coupling numerical calculation model for reinforced soil slopes and studied the effects of rainfall infiltration on the stress, displacement, and pore pressure of geogrid-reinforced soil slopes [17,18]. Zhang et al analyzed the seepage field distribution of root-fixed soil under rainfall conditions and found that when the root system continued to absorb water, the shear strength of unsaturated soil also increased [19,20].…”
Section: Introductionmentioning
confidence: 99%